2020
DOI: 10.1111/mec.15339
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics reveals divergent thermal selection in warm‐ and cold‐tolerant marine mussels

Abstract: Investigating the history of natural selection among closely related species can elucidate how genomes diverge in response to disparate environmental pressures. Molecular evolutionary approaches can be integrated with knowledge of gene functions to examine how evolutionary divergence may affect ecologically relevant traits such as temperature tolerance and species distribution limits. Here, we integrate transcriptome‐wide analyses of molecular evolution with knowledge from physiological studies to develop hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 125 publications
2
19
0
Order By: Relevance
“…While M. edulis has been shown to start their spawning in late spring, M. trossulus generally starts later in the summer [116,117], paving a possibility for M. trossulus to dominate areas with longer-lasting sea ice. Popovic and Riginos [118] summarized data on distribution and temperature of four Mytilus taxa in Northern Hemisphere and demonstrated that M. galloprovincialis inhabits waters characterized by much higher mean surface temperature in comparison with M. edulis and M. trossulus. M. galloprovincialis has physiological and metabolic adaptations to higher sea water temperature in comparison with M. edulis and M. trossulus [119][120][121][122].…”
Section: Relationships Between Mytilus Genotypes and Environmental Famentioning
confidence: 99%
See 1 more Smart Citation
“…While M. edulis has been shown to start their spawning in late spring, M. trossulus generally starts later in the summer [116,117], paving a possibility for M. trossulus to dominate areas with longer-lasting sea ice. Popovic and Riginos [118] summarized data on distribution and temperature of four Mytilus taxa in Northern Hemisphere and demonstrated that M. galloprovincialis inhabits waters characterized by much higher mean surface temperature in comparison with M. edulis and M. trossulus. M. galloprovincialis has physiological and metabolic adaptations to higher sea water temperature in comparison with M. edulis and M. trossulus [119][120][121][122].…”
Section: Relationships Between Mytilus Genotypes and Environmental Famentioning
confidence: 99%
“…Mantle transcriptome comparison among Mytilus taxa has been performed by Malachowicz and Wenne [123]. While Fraïsse et al [44] demonstrated some SNP loci under selection (outliers), Popovic and Riginos [118] used transcriptome analysis for temperature selection studies in Mytilus specimens from natural environments. Their study performed on 24 individuals of Mytilus congeners collected from natural environments differing in temperature suggested a positive temperature-dependent selection as a factor influencing molecular divergence between warm and cold tolerant Mytilus taxa.…”
Section: Relationships Between Mytilus Genotypes and Environmental Famentioning
confidence: 99%
“…Three contigs provided especially strong evidence for genetic parallelism following introduction, with high differentiation at the same nucleotide positions (max F ST > 0.4) when considering joint outcomes across both population pairs in permutation tests ( p < .001; Figure 2a). Suggestively, Contig33253 returned a top blastn hit to the M. galloprovincialis hsp90‐2 gene encoding heat‐shock protein 90 (HSP90); HSPs and other oxidative stress‐related proteins have been shown to evolve under positive selection in M. galloprovincialis (Popovic & Riginos, 2020) and may also be targets of repeated selection within introduced environments or during long‐distance transport experienced by migrant larvae in the ballast water of container ships.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental pressure might also favor the frequency of adaptive alleles at the scale of the population which would confer heritable changes modifications to specific environmental conditions. For instance, natural selection has contributed to the higher thermal tolerance and increased invasive potential of the blue M. galloprovencialis compared to other Mytilus species (Popovic & Riginos, 2020; Saarman, Kober, Simison, & Pogson, 2017). In C. gigas , natural selection and/or local adaption on thermal performances shaped the fine-scale structure of populations living in a highly-connected and temperature-contrasted area (Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%